DINAMIKA DEMOKRASI DI INDONESIA MASA ORDE LAMA: STUDI KASUS ANTARA SUKARNO VERSUS MASYUMI (History Department, Semarang State University and Historian Society of Indonesia, 2011)
The conflict between President Sukarno and Masyumi Party showed an increase from one period to the next. The intensity of the conflict is increasingly hard since the release of President Conception , and reach its peak during the guided democracy. Almost every statement and policy of Sukarno are always opposed by Masyumi. Vice versa, Sukarno judge the criticism as a form of defiance and resistance. The existence of a negative assessment of each party, and not ending conflict between the two sides, then worsen the relationship between Sukarno Masjumi. Masyumi assess Sukarno ignore the principles of democracy, and Sukarno judged that Masyumi is the enemy of guided democracy. The battle between Masyumi which is based on the attitudes and actions of constitutional democracy should end with Sukarno's policies and decisions to disband the Masyumi on behalf of democracy. Keywords: Masyumi, Sukarno, democracy, guided democracy Â